Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1182/blood-2007-06-098392
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 stimulates platelet aggregation by blocking the antithrombotic activity of nitric oxide/cGMP signaling

Abstract: Platelet alpha-granules constitute the major rapidly releasable reservoir of thrombospondin-1 in higher animals. Although some fragments and peptides derived from thrombospondin-1 stimulate or inhibit platelet aggregation, its physiologic function in platelets has remained elusive. We now show that endogenous thrombospondin-1 is necessary for platelet aggregation in vitro in the presence of physiologic levels of nitric oxide (NO). Exogenous NO or elevation of cGMP delays thrombin-induced platelet aggregation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
172
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(183 citation statements)
references
References 72 publications
7
172
1
Order By: Relevance
“…At nanomolar TSP1 concentrations, this inhibition can be mediated by CD36 (14), but at physiological circulating plasma TSP1 concentrations (100 -200 pM), CD47 is the necessary TSP1 receptor for inhibiting activation of soluble guanylate cyclase (20) or cGMP-dependent protein kinase (21). CD47-null and TSP1-null mice show similarly enhanced survival of full thickness skin grafts and increased angiogenic responses in the wound bed (22).…”
mentioning
confidence: 99%
“…At nanomolar TSP1 concentrations, this inhibition can be mediated by CD36 (14), but at physiological circulating plasma TSP1 concentrations (100 -200 pM), CD47 is the necessary TSP1 receptor for inhibiting activation of soluble guanylate cyclase (20) or cGMP-dependent protein kinase (21). CD47-null and TSP1-null mice show similarly enhanced survival of full thickness skin grafts and increased angiogenic responses in the wound bed (22).…”
mentioning
confidence: 99%
“…The NOinsensitive state of sGC persisted in cell-free lysates and was prevented by the protein kinase inhibitor staurosporine, which suggests that TSP1/CD47 signaling induces an inhibitory phosphorylation of sGC. Inhibition of sGC by TSP1 was first reported in endothelial cells, but subsequent studies have confirmed this result in VSMCs (96), platelets (95,162), T cells (202), and macrophages (206) of human and nonhuman origin, broadly implicating TSP1 as limiter of sGC activity.…”
mentioning
confidence: 82%
“…-/-and Cd47 -/-platelets showed clear defects in thrombin-mediated activation (95). Correspondingly, cGMP levels were elevated in Thbs1 -/-platelets but restored to normal levels by addition of exogenous TSP1 or a CD47-binding peptide.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, low NO concentrations have been seen to slightly potentiate thrombin‐induced Ca 2+ ‐elevations thus potentially contributing to platelet activation 61, 62. Platelet activators like thrombospondin‐1 (TSP1) have been shown to cross‐inhibit sGC through some unknown mechanism 63. Further studies are required to clarify interactions between different receptors, NO, sGC, cGMP, and Ca 2+ keeping in mind the methodological issues that might affect experiments on NO and cGMP pathways 64, 65…”
Section: Interactions At Receptor Levelmentioning
confidence: 99%